Participation and Performance in the Oldest Ultramarathon–Comrades Marathon 1921–2019 - Nikolaidis, Pantelis Theodoros; Knechtle, Beat; Vancini, RodrigoLuiz; Gomes, Margarida; Sousa, CaioVictor (International Journal of Sports Medicine, 2020)
Participation and performance trends have been analyzed for different ultramarathons for limited time periods. This study examined trends in participation and performance in the oldest ultramarathon in the world, the ‘Comrades Marathon’ (South Africa), during a century (1921−2019). Data from www.ultra-marathon.org on 100 000 unique finishers were analysed using different general linear models. Women represented 4.2% of the total sample (n=4152), and the first women ran this race in 1978. Before the year 1965, the number of participants in the race ranged between 5 and 35 athletes, then started to grow exponentially until mid 90’s. An increase in finishers in the 70 s mainly due to an increase in male athletes in age groups 30−39, 40−49 and 50−59 years was observed (p<0.001). A stable running speed for overall women and men but an improvement in performance for the annual top five women and men were shown (p<0.001). Male runners were faster than female runners for all age groups (p<0.001). While overall performance was not improved across years, the annual top five women and men were able to improve their performance over years.
Keywords: age group; performance analysis; race time; sex difference; ultra-endurance